Perencanaan Instalasi Pengolahan Air Limbah (IPAL) Domestik Central Processing Plant (CPP) Gundih PT. Pertamina EP Asset 4 Cepu Field - Hanuranti, Aviandini Galih; Nengse, Sulistiya; Pribadi, Arqowi; Nurmaningsih, Dyah Ratri; Utama, Teguh Taruna (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2020)
Central Processing Plant (CPP) Gundih is one of the production facilities of natural gas processing Blok Gundih PT. Pertamina EP Asset 4 Cepu Field from Kedungtuban, Randublatung, and Kedunglusi structure. Main activities of CPP Gundih consist production and operational activities. Production activities produces produced water. The water treatment of produced water processed by a production system and process. Operational activities of CPP Gundih produces wastewater from domestic activities (office) by 161 workers/day. The quantity of domestic wastewater are 21,896 m3/day, and the quality of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solid (TSS) are 9,8 mg/L, 100 mg/L, and 33 mg/L. Grey water and black water currently accommodated in septic tanks. Runoff from the septic tank flowed through drainage without treatment. Therefore, sewerage treatment plant planned with anaerobic-aerobic biofilter. The cost needed for the construction are Rp. 13.590.441,80-.